Pengaruh Set Kesempatan Investasi, Pertumbuhan Laba dan Konservatisme terhadap Kualitas Laba pada Perusahaan Terdaftar di Bursa Efek Indonesia - Siti Rofiqoh; Maftukhin; Roni; Dumadi; Slamet Bambang Riono (Journal of Accounting and Finance (JACFIN), 2020)
This study was conducted to obtain empirical evidence regarding the effect of investment opportunity sets, profit growth and conservatism on earnings quality with the object of research being trade, service and investment sector service companies listed on the IDX from 2015 to 2019. The method used to determine the sample in this study is by using a purposive side technique so that 41 companies are obtained from the total listed companies as many as 167 companies. The data processing analysis technique uses the SPSS application. The results show that the investment opportunity set has no effect on earnings quality. Meanwhile, profit growth and conservatism have a positive effect on earnings quality.